Storks’ Diversity, Flock Characteristic, Roosting Ecology and Fluctuation in Numbers in Some Mayas at Dinder National Park, Sudan, During the Dry Seasons 2009 and 2010 - Meina, Omer M.; Hashim, Ibrahim M. (University of Khartoum Journal of Agricultural Sciences, 2023)
Storks were studied by directly observing them in the Maya (meadow) ecosystem of Dinder National Park (DNP) during the dry seasons of 2009 and 2010. The objective was to determine their diversity, flock characteristics, roosting ecology and the annual fluctuation in their numbers. The numbers were ascertained by the double sampling procedure in which the number of each stork species in a flock was estimated and was then directly counted. A predictive model was developed from the relationship between the counted and the estimated variables. Subsequently, the number was only estimated and the actual count was predicted from the regression model. The tree density was determined by the nearest neighbour method. The crown diameters of the trees were measured, and the crown areas were calculated. Eight species of storks; namely, the black (Ciconia nigra), the white (Ciconia ciconia), the Abdim’s (Ciconia abdimii), the yellow-billed (Mycteria ibis), the African open bill (Anastomus lamelligerus), the woolly-necked (Ciconia episcopus), the marabou (Leptoptilos crumeniferus) and the saddle bill (Ephippiorhynchus senegalensis), occurred in DNP. The black and the white storks are Palearctic migrants, whereas the Abdim’s, the woolly- necked, the African open bill and the yellow-billed are local migrants; the marabou and the saddle bill are resident. The three species that occurred in large flocks were the yellow-billed, the marabou and the open bill. The total number of storks in 2010 was lower than that in 2009. This decline was attributed to severe drought that struck the DNP in 2010.